Retroalimentación formativa y logros de aprendizaje en el área de desarrollo personal ciudadanía y cívica en estudiantes del Quinto Grado de Secundaria de la Institución Educativa Colegio Nacional Iquitos 2023 - Lopez Rios, Jenrry Segundo (2024)
The study's task was to establish the link between formative feedback and learning achievements in basic education students. It assumed the quantitative approach with a correlational level of research. The study unit included 141, from which a sample of 104 students from 5th H, I, J and K was drawn with 26 participants per classroom. To gather information on the work variables, a questionnaire was used as an instrument. The most important results show that, with an error level of 0.0%, there is a strong correlation between formative feedback and learning achievements. These data confirm a statistically significant relationship between formative feedback and learning achievements in personal development, citizenship and civics students in the fifth grade of secondary school at the Colegio Nacional Iquitos 2023 educational institution